A New Control Method for Using Inkjet Printer Motherboard as 3 Axes CNC Router's Motion Control Card - Buyuksahin, Utku (TRANS TECH PUBLICATIONS LTD, 2012)
As the inkjet printers have two axes of movement, (one for scrolling of the paper and one for travelling of the cartridges) inkjets have closed loop stepper motor control cards for two axes which can be used in CNC routers. There are few studies in literature and internet about this method. The main difficulty while using these cards as motion control card is to send the motion data of the cutting process to the CNC's motor drivers. As programming ability is needed, this is the point where the projects are mostly left unfinished. In this study, a new method to help use of printer motherboards as CNC router motion control cards, with no need of programming skills and buying expensive software, is given. In this method, the third dimension of the picture is represented by colors. After drawing the two dimensional top view of the workpiece with any simple graphics painting software which can be found in every computer like Paint, is painted with the colors black to white, from the lowest level to highest respectively, like in the geographical maps which the oceans are painted darker to lighter according to the depth. As it is known that there are 16.7 millions of colors between black and white, the system is impressively precise in Z axis. The analogue signals of the colors which are sent from printer's motherboard to the cartridges are captured with a PIC based circuit, which is designed for this project. Then the color codes are converted to Z axis's position data and PWM signals that are needed in Z axis motion. The X and Y axes' stepper motor control PWM signals are generated by printer motherboard and used in the system just as is. While doing the cutting process on a printer motherboard attached CNC, the computer assumes as if a picture is being printed with the printer that is connected to USB or parallel port. This method is candidate to be one of the most common used home based or laboratory based CNC control methods in the near future.
Keywords: CNC control unit; Printer motherboard to motion control card; Engineering; Materials Science